The invasion of Central Europe by Senecio inaequidens dc. - A complex biogeographical problem - Heger, Tina; Böhmer, Hans Jürgen (ERDKUNDE, 2005)
Since the 1970´s, the neophyte Narrow-leafed Ragwort (Senecio inaequidens DC.) has spread rapidly in Central Europe, particularly in Germany. The species grows on roadsides and railway embankments, on urban wasteland, slag heaps, construction sites and other disturbed locations. This study reviews literature on the invasion of S. inaequidens in Central Europe with a focus on Germany, and analyses the factors determining the species´ success. The analysis is based on a conceptual invasion model, termed the model of invasion steps and stages (INVASS model). Using an organism-centred approach, the model names problems which may arise during a plant invasion. The present study discusses factors which may have influenced the spreading of S. inaequidens. Species characteristics and favourable conditions contributing to the success of the invasion steps are named. Unresolved questions are identified, and major subjects for further research are recommended.